2014
DOI: 10.1615/jenvironpatholtoxicoloncol.2014011075
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Molecular Events of Cadmium-Induced Carcinogenesis

Abstract: Cadmium (Cd) is a toxic, heavy industrial metal that poses serious environmental health hazards to both humans and wildlife. Lately, Cd and Cd containing compounds have been classified as known human carcinogens and epidemiological data show causal associations with prostate, breast and lung cancer. The molecular mechanisms involved in Cd-induced carcinogenesis are poorly understood and are only now beginning to be elucidated. The effects of chronic exposure to Cd have recently become of great interest due to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
102
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(112 citation statements)
references
References 73 publications
2
102
0
2
Order By: Relevance
“…In vivo, Cd mimics the effect of estrogens in the uterus and mammary gland, stimulates proliferation in estrogen-responsive breast cancer cell lines and can activate the ER independent of estradiol [201]. Various in vitro studies demonstrated that Cd can act as a mitogen, can stimulate cell proliferation and inhibit apoptosis and DNA repair and can induce carcinogenesis in several mammalian tissues and organs [202]. Gallagher et al [203] examined the association of breast cancer with urinary Cd in a case-control sample of women living on Long Island (NY), a region with an especially high rate of breast cancer and in a representative sample of US women in a multivariable logistic model.…”
Section: Metalsmentioning
confidence: 99%
“…In vivo, Cd mimics the effect of estrogens in the uterus and mammary gland, stimulates proliferation in estrogen-responsive breast cancer cell lines and can activate the ER independent of estradiol [201]. Various in vitro studies demonstrated that Cd can act as a mitogen, can stimulate cell proliferation and inhibit apoptosis and DNA repair and can induce carcinogenesis in several mammalian tissues and organs [202]. Gallagher et al [203] examined the association of breast cancer with urinary Cd in a case-control sample of women living on Long Island (NY), a region with an especially high rate of breast cancer and in a representative sample of US women in a multivariable logistic model.…”
Section: Metalsmentioning
confidence: 99%
“…The environmental exposure in the long time to Cd acts like a carcinogenic agent at the human ones [2,3].According to conditions' of exposure to metal (food or nicotine), 5% of introduced cadmium are absorbed by the gastro-intestinal tract in salt form, while 90% of inhaled cadmium are absorbed by pulmonary way [4]. The nicotine constitutes a significant cadmium contribution (approximately 1μg by cigarette) [5].…”
Section: Introductionmentioning
confidence: 99%
“…The studies so far reported that cadmium impairs p53 activity by inhibiting its DNA binding capacity leading to faulty DNA replication causing cadmium-induced carcinogenesis. This happens when cells are exposed to concentration of cadmium, lower than that can inhibit cell viability (Giaginis et al 2006;Luevano & Damodaran 2014). Cadmium is found to induce p53-mediated apoptosis at cytotoxic concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…Cadmium is found to induce p53-mediated apoptosis at cytotoxic concentrations. Hampering p53 activation has shown to inhibit apoptosis in cadmium-exposed cells (Aimola et al 2012;Luevano & Damodaran 2014).…”
Section: Introductionmentioning
confidence: 99%